OPTIMIZING MATHEMATICAL PROBLEM-SOLVING SKILLS AMONG STUDENT THROUGH METACOGNITIVE-BASED TEACHING MATERIALS DEVELOPMENT - Liyana Sunanto; Mahpudin (Jurnal Cakrawala Pendas, 2023)
This research was conducted to obtain lecture tools (syllabus, SAP, textbooks and worksheets) that use metacognitive strategies, and see the effectiveness of lecture tools in shaping students' abilities to solve mathematical problems. The research design used is ADDIE development research. This research will be conducted on third semester students of the PGSD study program, Faculty of Education and Humanities, Pelita Bangsa University, TA 2022/2023 in the Elementary Mathematics Learning course. This teaching material is declared valid based on the validation results of experts, practitioners and media experts which are marked by the acquisition of a hih score so that it is suitable for use. Penelitian ini dilakukan untuk mendapatkan perangkat perkuliahan (silabus, SAP, buku ajar dan LKS) yang menggunakan strategi metakognitif, serta melihat keefektifan perangkat perkuliahan dalam membentuk kemampuan mahasiswa dalam memecahkan masalah matematika. Desain penelitian yang digunakan adalah penelitian pengembangan ADDIE. Penelitian ini akan dilakukan pada mahasiswa semester tiga program studi PGSD Fakultas Pendidikan dan Ilmu Budaya Universitas Pelita Bangsa TA 2022/2023 pada mata kuliah Pembelajaran Matematika SD. Bahan ajar ini dinyatakan valid berdasarkan hasil validasi ahli, praktisi dan ahli media yang ditandai dengan perolehan skor hih sehingga layak digunakan.